Diversidade genética em população de melhoramento de mogno africano (Khaya ivorensis A. Chev.) - Soares, Sabrina Delgado (2014)
The strong demand for hardwood drives selective logging and degradation of forests ecossystems in Brazil. Due to its wood value and predatory logging, Brazilian mahogany (Swietenia macrophylla) is at risk of extinction. Currently, its trees are protected and banned from logging by the Brazilian Institute of Environment (IBAMA). Monoculture of the Brazilian mahogany is proven unsuccessful due to the attack of the Hypsipyla grandella larvae. An alternative to Brazilian mahogany plantation is the African mahogany (Khaya ivorensis), a species with similar high valued wood properties. The Universidade Federal de Goiás in partnership with Mudas Nobres Company started a breeding program with Khaya ivorensis. The objective of this study was to evaluate the genetic diversity and divergence among 53 superior trees selected and cloned as part of the breeding strategies. Clones were selected from three different populations, planted in two farms in Pará state and originating from Ivory Coast and Tanzania populations. Twelve seedlings of Khaya senegalensis were also used as a control group in the analyses of genetic divergence. The individuals were genotyped with eight microsatellite loci developed for K. senegalensis, by capillary electrophoresis on the ABI-3100 (Applied Biosystems) platform. The software GeneMapper (Applied Biosystems) was used to genotype the alleles. The average number of alleles per locus was 5.875. The average expected heterozygosity was lower (HE = 0.563) than the average observed heterozygosity (HO = 0.738). Therefore, the average intrapopulation fixation index was negative (f = - 0.314) indicating that high inbreeding depression is decreasing the frequency of homozygous when compared to what would be expected under Hardy-Weinberg Equilibrium. The average fixation index between populations was estimated at θ = 0.008, indicating that only 0.8% of the genetic variability is due to differences between populations. The dendrogram generated from the matrix of Rogers’ genetic distance showed two distinct groups, separating the control group with K. senegalensis from the K. ivorensis selected trees. The group composed of K. ivorensis had nodes with weak bootstrap consistency indicating weak genetic structure among selected trees. The lack of genetic structure was confirmed by a Bayesian approach on the Structure (version 2.3.4) program. The genetic diversity observed within the selected breeding population is comparable to that of natural populations of African and Brazilian mahoganies. The genetic distance estimated with this work will guide the selection of divergent progenitors to be crossed.